2012
DOI: 10.1002/app.36823
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the mechanical properties of notched aluminum—epoxy particulate composites

Abstract: The aim of the present investigation is to study both the influence of particle weight fraction (0-50%) and the effect of the notch length on the static mechanical properties of aluminum particle epoxy composites. Experimental results in both cases were compared with three different theoretical models, previously developed by the first author and presented in a series of publications. First, for the evaluation of the maximum strength the particle sectioning model (PSM) was applied. Next, for the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…As observed clearly in Figure (a) the adhesion between the filler and the matrix is bad. In general, the main disadvantage of natural filers as reinforcements to polymer matrices is the poor compatibility between filler and matrix and their relative high moisture absorption …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed clearly in Figure (a) the adhesion between the filler and the matrix is bad. In general, the main disadvantage of natural filers as reinforcements to polymer matrices is the poor compatibility between filler and matrix and their relative high moisture absorption …”
Section: Resultsmentioning
confidence: 99%
“…These findings were experimentally verified through both SEM photography and relevant sources as taken from Refs. . It was proved that the RPM model predicted perfectly well and much better than the two other models the stress relaxation behavior of the composites investigated and above all it can predict well both the linear and the nonlinear viscoelastic behavior. Finally, it was found that the relaxation times as calculated from the RPM model application, depend both on the applied deflection and the filler weight fraction.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be explained for the solid particles are sharing a larger portion of the load than the comparatively soft matrix [42]. Moreover, the Al particles have much higher modulus in comparison with polymer and so as volume fraction is increasing, the initial modulus of the propellant is increasing too [43].…”
Section: Effect Of Al Contentmentioning
confidence: 99%
“…[21][22][23] In the present work, the RPM has been applied in order to predict the residual compressive strength of five different materials systems as a function of the additives concentration. In all cases and independently of the material system under consideration, function M was found as: M ¼ C 2 , where C is the percentage concentration of the phase added.…”
Section: The Rpm Model Presentation and Applicationmentioning
confidence: 99%
“…The RPM model has already been successfully applied to all the above-mentioned cases as well as to many others such as materials property degradation after thermal shock cycling, and strength reduction due to materials discontinuities (central hole, edge cracking, etc.). 2123…”
Section: Residual Property Modeling and Porosity Estimationsmentioning
confidence: 99%